Cemil Topuzlu Pacha and his arterial suture technique - (:unkn) unknown (ELSEVIER SCIENCE INC, 1997)
Cemil Topuzlu Pacha (1868-1958) is known to be one of the most famous surgeons in Turkey through the early decades of the twentieth century. Being a talented and courageous surgeon, he performed many of the avoided operations of that time. He presented his vascular suture techniques at the International Medical Congress in Moscow in August 1897 and at the annual Congress of the Societe de Chirugie de Paris in July 1904. He reported 2 cases of arterial tear during breast carcinoma resection and repair within the same session. He also reported the removal of a pen covet from the right main bronchus of a 7-year-old girl through a tracheotomy in 1903. He worked for 3 years with the famous French surgeon Jules Pean and became a preferred surgeon of the Ottoman Imperial family in Instanbul. He was admired for his scientific studies in international congresses and was one of the first Turkish surgeons who became a member of important European surgical associations. (C) 1997 by The Society of Thoracic Surgeons.